Preliminary Study Of Agrobacterium-Mediated Transformation With Polyhydroxyalkanoate Genes For Rubber Tree Hevea Brasiliensis Muell. Arg. Clone Pb 350 - Lim, Kok Ming (2022)
Hevea brasiliensis (H. brasiliensis), better known as rubber tree, is the main producer of natural rubber. H. brasiliensis clone PB 350 is one of the clones recommended by the Malaysian Rubber Board (MRB) as a high yielding latex timber clone (LTC). This clone is a good candidate for heterologous protein production because it can produce high amount of latex from where the heterologous protein could potentially be harvested from. Polyhydroxyalkanoate (PHA) is a biodegradable bioplastic produced by prokaryotes. While PHA has the potential to replace conventional plastics, the high cost of production makes it not feasible. Thus, attempts had been made to generate PHA-producing transgenic plants because carbon sources for heterologous protein production in plant comes from freely available carbon dioxide in the air and can potentially lower the production cost. Eventhough previous studies have reported on the transformation of H. brasiliensis, the transformation efficiency of different rubber clones differ. Therefore, the aim of this study was to determine suitable parameters to produce transgenic H. brasiliensis clone PB 350 capable of expressing the PHA biosynthetic genes. This study began with the screening for suitable explants for transformation.